River of secrets eaudiobook - Eason, Lynette (Refuge from Danger, 2019)
Amnesia and danger collide in this classic tale from bestselling author Lynette Eason. The amnesiac patient in the makeshift Amazon hospital looks familiar to visiting American nurse Amy Graham. This isn't the first time she's seen those blue-gray eyes, the hard lines of his handsome face. When Amy sees his birthmark, she knows exactly who he is: Micah McKnight, the presumed-dead Navy SEAL. Her best friend's brother. The man her own mother set up to die. Amy can't bear to tell him the dangerous truth about his hidden past. But her secrets are about to explode, because now someone is after them both.